ANALISIS NILAI TAMBAH MINYAK SERAI WANGI DI KECAMATAN SAWANG KABUPATEN ACEH UTARA - Irhas, Irhas; Talyani, Talyani; Suryadi, Suryadi; Riani, Riani (LPPM Universitas Malikussaleh - Indonesia, 2022)
Lemongrass is one of the most prospective essential commodities. The demand for citronella oil is quite high and the price is stable and tends to increase. Distilled citronella leaves produce an essential oil known as Citronella oil. In Aceh Utara, the production of citronella farming and agroindustry is focused on Sawang Sub-District. The establishment of an agroindustry for refining citronella oil is one of the ways in which existing citronella can be processed into citronella oil. Processing is in order to provide maximum benefits by paying attention to aspects of efficiency and effectiveness, namely increasing added value. The purpose of this study was to analyze the potential of agro-industry and added value in the citronella processing agroindustry in Sawang District, North Aceh Regency. Added value analysis is by using the Hayami method. The results showed that the potential for citronella agro-industry in North Aceh District was relatively limited given the limited raw materials for citronella. The distillery still uses oil drums so that the quality of the oil produced allows it to contain iron carotene. The added value in 1 Kg of citronella raw material is IDR 799 /Kg, meaning that for every 1 Kg of raw material will provide an additional value of IDR 799. While the added value ratio of citronella oil is 49.93%. The distillery still uses oil drums so that the quality of the oil produced allows it to contain iron carotene